ANALISIS PENGARUH PDB, NILAI TUKAR RUPIAH, NON PERFORMING FINANCE (NPF), BOPO TERHADAP PROFITABILITAS (ROA) PERBANKAN SYARIAH DI INDONESIA PERIODE 2008-2013 - Putri Asrina; Syapsan '; Anthoni Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of the influence of GDP,Exchange rate, NPF,Ratio Operational Cost for Operational Income to the Return on Asset of Islamic Banking. The data used in this study is a time series data from 2008 to 2013. The samples are all of BUS and UUS in Indonesia. The method used in this study, namely multiple linier regression with Eviews 3.0. This study tested the hypothesis of regression coefficient (coefficient of determination, a significant test concurrent/F test, and the significant individual test / t test). The result showed that the variable GDP,exchange rate, NPF, Ratio operational cost for operational income at once / simultaneously have a significant influence on the realitation Return on Asset (ROA) of Islamic Banking . The individual test/partial showed that ratio Operational cost for operational income variable acquired that contributes greater than the variable GDP, exchange rate,and NPF on the realitation return on asset of Islamic Banking in Indonesia. The amount of influence that caused (R2) in the return on asset Islamic Banking of 57,2864%. While the remaining 42,7136% is influenced by othervariables not included in thestudy.Keywords: Return On asset, GDP, Exchange rate, NPF, Ratio Operational cost for Income Operational.